Recent Advances in Surface Functionalized 3D Electrocatalyst for Water Splitting - Nadira Meethale Palakkool; Mike P. C. Taverne; Owen Bell; Jonathan D. Mar; Vincent Barrioz; Yongtao Qu; Chung‐Che Huang; Ying‐Lung Daniel Ho (Advanced Energy & Sustainability Research)
Hydrogen is gaining attention as a fossil fuel alternative due to its potential to meet global energy demands. Producing hydrogen from water splitting is promising as a clean and sustainable fuel pathway. The hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) are crucial in electrocatalytic water splitting for energy conversion and storage. However, water electrolysis faces challenges in cost, efficiency, and scalability. Alternative transition metal electrocatalysts and emerging 2D materials advance electrolysis research, though transitioning from academia to industry remains challenging. The introduction of 3D‐printing technologies has revolutionized electrode fabrication for HER and OER. This review explores integrating 3D‐printing technologies and surface functionalization with non‐noble metal‐based electrocatalysts and emerging 2D materials. It focuses on surface‐functionalized 3D‐printed electrodes using technologies like selective laser melting, stereolithography, and fused deposition modeling with non‐noble metal electrocatalysts such as transition metal oxides, hydroxides, and emerging 2D materials like transition metal carbide/nitride (MXenes) and transition metal dichalcogenides (TMDCs). The review highlights the opportunities and challenges in scalable fabrication, long‐term durability, and cost‐efficiency for practical implementation. Future research directions include exploring new materials for 3D printing and alternative electrocatalysts alongside leveraging theoretical and machine‐learning approaches to accelerate the development of competitive materials for water electrolysis.